2005
DOI: 10.1097/01.ccm.0000163246.33366.51
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine reduces nitric oxide biosynthesis in human umbilical vein endothelial cells by down-regulating endothelial nitric oxide synthase expression and intracellular calcium levels*

Abstract: A clinically relevant concentration of ketamine can reduce NO biosynthesis. The suppressive mechanisms occur not only by pretranslational inhibition of eNOS expression but also by a posttranslational decrease in endothelial NO synthase activity due to a reduction in intracellular calcium levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 37 publications
(43 reference statements)
3
30
0
4
Order By: Relevance
“…In hepatocytes, CYP3A4 is a major enzyme that participates in the metabolism of xenobiotics (Martínez-Jiménezet al, 2007). Our previous studies showed that a therapeutic concentration of ketamine can suppress macrophage activities and reduce endothelial nitric-oxide synthesis (Chang et al, 2005;Chen et al, 2005). In this study, we further demonstrated that clinically relevant concentrations of ketamine can lead to dysfunction of HepG2 cells due to suppression of cytoskeletal remodeling, calcium mobilization, ATP synthesis, and enzyme activity rather than the death mechanism.…”
Section: Discussionmentioning
confidence: 54%
“…In hepatocytes, CYP3A4 is a major enzyme that participates in the metabolism of xenobiotics (Martínez-Jiménezet al, 2007). Our previous studies showed that a therapeutic concentration of ketamine can suppress macrophage activities and reduce endothelial nitric-oxide synthesis (Chang et al, 2005;Chen et al, 2005). In this study, we further demonstrated that clinically relevant concentrations of ketamine can lead to dysfunction of HepG2 cells due to suppression of cytoskeletal remodeling, calcium mobilization, ATP synthesis, and enzyme activity rather than the death mechanism.…”
Section: Discussionmentioning
confidence: 54%
“…24 Briefly, osteoblasts (2 Â 10 4 ) were seeded in 96-well tissue culture plates overnight. After drug treatment, osteoblasts were cultured with new medium containing 0.5 mg/mL 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide for a further 3 h. The blue formazan products in osteoblasts were dissolved in dimethyl sulfoxide and spectrophotometrically measured at a wavelength of 550 nm.…”
Section: Assay Of Cell Viabilitymentioning
confidence: 99%
“…Ogawa et al [57] zeigten an Pulmonalarterienringen von Kaninchen, dass Ketamin der durch Acetylcholin und Bradykinin induzierten Vasodilation über eine Hemmung von NOund "endothelium-derived hyperpolarizing factor" (EDHF)-vermittelten Metaboliten entgegenwirkt. In einer kürzlich von Chen et al [15] publizierten Studie wurde der Einfluss von Ketamin auf die Vasoregulation über das NO-cGMP-System genauer untersucht: An Endothelzellen aus menschlichen Umbilikalvenen, die mit unterschiedlichen Konzentrationen von Ketamin inkubiert wurden, konnte demonstriert werden, dass Ketamin in therapeutischen Dosierungen die NO-Biosynthese reduziert. Des Weiteren berichtete dieselbe Arbeitsgruppe, dass die NO-Synthesehemmung nicht nur auf einer prätransla-tionalen Inhibition der eNOS-Expression beruht, sondern auch auf einer Ca 2+ -abhängigen poststranslationalen Reduktion der eNOS-Aktivität.…”
Section: Interaktion Mit Dem No-cgmp-systemunclassified